Lung Metastasectomy from Colorectal Cancer, 10-year Experience in a South American Cancer Center - Carvajal Fierro, Carlos A.; Facundo-Navia, Helena; Puerto, Paola; Carreno, Jose; Beltran, Rafael (Frontiers in Surgery, 2022)
Purpose This study aimed to describe the survival outcomes and factors associated with prognosis in patients undergoing pulmonary metastasectomy with colorectal cancer (CRC) in a cancer center in South America. Material and methods A retrospective analysis of patients that underwent lung metastasectomy due to CRC at National Cancer Institute (INC), Colombia between 2007 and 2017 was performed and Kaplan-Meier survival analysis along with log-rank test and Cox regression multivariate analysis were completed. Results Seventy-five patients with colorectal adenocarcinoma were included in the study. Of them, 57.3% were women with a median age of 62 years [interquartile ranges (IQR): 18.5]. For 45.3% the adenocarcinoma was located in the rectum and 29.3% had stage IV at diagnosis. 56% had a history of controlled extrapulmonary metastasis and 20% of the cases had a history of the metastasis of the liver. The median follow-up was 36.8 months (IQR: 27.4). Three-year and five-year overall survival (OS) was 57.5% [95% confidence interval (CI), 47.0–70.4] and 33.2% (95%CI, 23.4–47.2), respectively. Patients with bilateral, more than one pulmonary metastasis, abnormal postmetastasectomy carcinoembryonic antigen (CEA), history of liver metastasis, and disease-free interval (DFI) ≤12 months had worse OS. Three-year and five-year disease-free survival (DFS) was 30.1% (95%CI, 20.8–43.6) and 21.6% (95%CI, 13.0–35.9), respectively. Bilateral, more than one pulmonary metastasis, and patients with stage IV at diagnosis had the worst DFS. Multivariate analysis in the Cox regression model showed that abnormal postmetastasectomy CEA [Hazard Ratio (HR):1.97, 95%CI, 1.01–3.86, P=0.045] and DFI≤12 months (HR: 3.08, 95%CI, 1.26–7.53, P=0.014) were independent factors for worst OS. Conclusions The OS found falls within the wide range described in the world literature but interestingly it falls at the bottom end of this range. The factors associated with worst survival were identified as bilateral, more than one pulmonary metastasis, abnormal postmetastasectomy CEA, history of liver metastasis, and DFI ≤12 months.